2021
DOI: 10.3390/cells10123415
|View full text |Cite
|
Sign up to set email alerts
|

The Fusion Protein rFlaA:Betv1 Modulates DC Responses by a p38-MAPK and COX2-Dependent Secretion of PGE2 from Epithelial Cells

Abstract: Developing new adjuvants/vaccines and better understanding their mode-of-action is an important task. To specifically improve birch pollen allergy treatment, we designed a fusion protein consisting of major birch pollen allergen Betv1 conjugated to the TLR5-ligand flagellin (rFlaA:Betv1). This study investigates the immune-modulatory effects of rFlaA:Betv1 on airway epithelial cells. LA-4 mouse lung epithelial cells were stimulated with rFlaA:Betv1 in the presence/absence of various inhibitors with cytokine- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…117 Classically regarded as a pro-inflammatory mediator, PGE2 (prostaglandin E2) can promote resolution. 118 PGE2 by inhibiting the proliferation, activation, and secretion of cytokines by ILC2. 119 Studies in asthmatic patients reported an inverse correlation between the sputum levels of PGE2 and eosinophil numbers, thus suggesting it can play a role in reducing airway eosinophilia.…”
mentioning
confidence: 99%
“…117 Classically regarded as a pro-inflammatory mediator, PGE2 (prostaglandin E2) can promote resolution. 118 PGE2 by inhibiting the proliferation, activation, and secretion of cytokines by ILC2. 119 Studies in asthmatic patients reported an inverse correlation between the sputum levels of PGE2 and eosinophil numbers, thus suggesting it can play a role in reducing airway eosinophilia.…”
mentioning
confidence: 99%
“…As a model for such novel therapeutics in the field of allergies, we generated a recombinant fusion protein, rFlaA:Betv1, that combines the TLR5-ligand flagellin A from Listeria monocytogenes with the major birch pollen allergen Bet v 1 into a single molecule [ 3 ]. In previous studies, we were able to show that rFlaA:Betv1 efficiently suppressed allergic sensitization in vivo [ 3 ] while also activating myeloid DCs (mDCs) [ 3 , 4 ], macrophages [ 5 ], epithelial cells [ 6 ], and B cells [ 7 ], leading to pro-inflammatory cytokine production and the subsequent formation of allergen-specific TH1 responses with TH2-suppressing capacity [ 3 , 5 ]. Furthermore, rFlaA:Betv1 induced a prominent production of the anti-inflammatory cytokine IL-10 in all investigated types of antigen presenting cells (APCs) (mDCs, macrophages, and B cells), which was shown to significantly suppress TH2 responses [ 3 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two articles with original data on the experimental production of novel recombinants of the major birch pollen allergen Betv1 have been published by a German team [ 5 , 6 ]. A recombinant fusion protein of flagellin A (serving as a TLR5-ligand) and Betv1, namely rFlaA:Betv1, has been produced, to target immune cells, in order to create adjuvant-mediated pro- and anti-inflammatory responses and suppress the allergen-induced Th2 responses [ 5 ].…”
mentioning
confidence: 99%
“…Using a mouse-model, the stimulation of bone marrow-derived macrophages (BMDMs) by rFlaA:Betv1 and the boosted IL-10 and INF-γ secretion in BMDM and T cell co-cultures, suggest an important role of macrophages as target cells of immunotherapy [ 5 ]. The immune-modulatory effects of rFlaA:Betv1 were confirmed in cultures of murine airway LA-4 epithelial cells with myeloid dendritic cells (mDC) [ 6 ]. It was shown that, upon stimulation with rFlaA:Betv1, epithelial cells can modulate pro-inflammatory mDC responses by p38 MAPK- and COX2-dependent production of PGE2 [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation